PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Ratih Partiwi; Herawati Herawati (Jurnal Kajian Akuntansi dan Auditing, 2022)
This research aims to determine the effect of institutional ownership, leverage, and company size on company performance in manufacturing companies listed on Indonesian Stock Exchange during 2016-2020. By using purposive sampling method, the sample were 48 manufacturing companies listed on the IDX. The data in this research are secondary data from www.idx.co.id. The results show that institutional ownership has no effect on company performance, leverage has a significant negative effect on company performance, while company size has a significant positive effect on company performance.